INOVASI PEMBELAJARAN BERDIFERENSIASI BERBANTUAN PEMANFAATAN TEKNOLOGI APLIKASI STORY.COM DAN WORDWALL PADA PEMBELAJARAN IPAS KELAS 5 SEKOLAH DASAR - Sri Rahayu; Erni Suharini rahayu; Hamdan Tri Atmaja (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to overcome the challenges in learning science and social science (IPAS) in grade 5 primary schools, especially in the material "Bumiku Sayang, Bumiku Malang" for semester 1, topic B. The main problem identified is the low level of student engagement and understanding of the material taught. To overcome this problem, this research proposes differentiated learning innovations using technology, namely the AI applications Story.com and Wordwall. The aim of this research is to evaluate the effectiveness of technological approaches in increasing student engagement, enriching the learning experience and facilitating deeper understanding of the material. The methodology used is a qualitative approach with a case study design involving 28 grade 5 students in a Pesurungan Kidul 1 primary school. Data was collected through classroom observations, interviews with teachers and students, and analysis of student learning outcomes. The research results show that the use of AI Story.com and Wordwall in differentiated learning significantly increased student engagement. Students show greater interest in the material and their learning outcomes improve. This technology allows teachers to tailor learning to individual student needs, which has a positive impact on understanding and retention. The conclusion of this research is that differentiated learning innovations using technology can be an effective solution for improving the quality of science and science learning in primary schools. Recommendations are made for the wider use of this technology in primary curricula to support more interactive and effective learning. Keywords: differentiated learning, technology, natural and social sciences